Timing of cardiac surgery and other intervention among children with congenital heart disease: A review article - JM, Chinawa; KD, Adiele; FA, Ujunwa; VO, Onukwuli; I, Arodiwe; AT, Chinawa; EO, Obidike; BF, Chukwu (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Early diagnosis and improved facilities are necessary for determining the optimal timing of surgery and other interventions in children with congenital heart diseases in Nigeria. This is because late presentation, late diagnosis and delayed surgery can lead to mortality and affect the quality of life among these children. Objectives: This review article is aimed at enumerating the timing of cardiac surgeries and other interventions and to seek if there is any factor associated with the timing of cardiac surgery. Methods: A search on PubMed database, World Health Organization libraries, Google scholar, TRIP database, and reference lists of selected articles on timing of cardiac surgery in children was done. The Cochrane Database of Systematic Reviews was also searched. We noted few data from African setting. Key words such as timing of cardiac surgery; children, congenital heart defect were used. Conclusion: Appropriate timing for cardiac surgery in children with congenital heart disease is very important as late surgical intervention could result in several morbidities and mortality.